Arrhythmia Patterns in Patients on Ibrutinib - Fazal, Muhammad; Kapoor, Ridhima; Cheng, Paul; Rogers, Albert J.; Narayan, Sanjiv M.; Wang, Paul; Witteles, Ronald M.; Perino, Alexander C.; Baykaner, Tina; Rhee, June-Wha (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Ibrutinib, a Bruton’s tyrosine kinase inhibitor used primarily in the treatment of hematologic malignancies, has been associated with increased incidence of atrial fibrillation (AF); with limited data on its association with other tachyarrhythmias. There are limited reports that comprehensively analyze atrial and ventricular arrhythmia burden in patients on ibrutinib. We hypothesized that long-term event monitors could reveal a high burden of atrial and ventricular arrhythmias in patients on ibrutinib. Methods: A retrospective data analysis at a single center using electronic medical records database search tools and individual chart review was conducted to identify consecutive patients who had event monitors while on ibrutinib therapy. Results: 72 patients were included in the analysis with a mean age of 76.9±9.9 years and 13 patients (18%) carrying a diagnosis of AF prior to the ibrutinib therapy. During ibrutinib therapy, most common arrhythmias documented were non-AF supraventricular tachycardia (n=32, 44.4%), AF (n=32, 44%), and nonsustained ventricular tachycardia (n=31, 43%). 13 (18%) patients had >1% premature atrial contraction burden; 16 (22.2%) patients had >1% premature ventricular contraction burden. In 25% of the patients, ibrutinib was held because of arrhythmias. 8.3% of patients were started on antiarrhythmic drugs during ibrutinib therapy to manage these arrhythmias. Conclusions: In this large dataset of ambulatory cardiac monitors on patients treated with ibrutinib, we report a high prevalence of atrial and ventricular arrhythmias, with a high incidence of treatment interruption secondary to arrhythmias and related symptoms. Further research is warranted to optimize strategies to diagnose, monitor, and manage ibrutinib-related arrhythmias.